2017
DOI: 10.1063/1.5007073
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ferromagnetic transitions and the temperature dependence of magnetic behaviors in FeCoNiCr-based high-entropy alloys

Abstract: High-entropy alloys (HEAs) containing multiple principle alloying elements exhibit unique properties so they are currently receiving great attention for developing innovative alloy designs. In FeCoNi-based HEAs, magnetic behaviors strongly depend on the addition of alloying elements, usually accompanied by structural changes. In this work, the effect of non-magnetic components on the ferromagnetic transition and magnetic behaviors in equiatomic FeCoNiCrX (X=Al, Ga, Mn and Sn) HEAs was investigated. Alloy ingot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Comparing the calculated Curie Temperature with those found in literature 7,13 , it lies within the CoFeNiCr x system, where for x = 0.9 and 0.7 the T c = 300 and 200 K respectively. Kormann et al 's 8 theoretical calculations shows that M s experiences a 68% increase from 0.55 to 0.93 μB (54-91 Am 2 /kg) in CoFeNiCr x on Cr x reduction from x = 1 to x = 0.5 and an increase in T c from 119 to 418 K. However, Kormann's CoFeNiCr 0.5 -M s of 91 Am 2 / kg is higher than our synthesised n-Al 0 sample (58 Am 2 /kg, taken from M-H loop at 400 kA/m and 100 K) .…”
Section: Microstructural Characterisation Figure 2 Indicates the Larsupporting
confidence: 75%
“…Comparing the calculated Curie Temperature with those found in literature 7,13 , it lies within the CoFeNiCr x system, where for x = 0.9 and 0.7 the T c = 300 and 200 K respectively. Kormann et al 's 8 theoretical calculations shows that M s experiences a 68% increase from 0.55 to 0.93 μB (54-91 Am 2 /kg) in CoFeNiCr x on Cr x reduction from x = 1 to x = 0.5 and an increase in T c from 119 to 418 K. However, Kormann's CoFeNiCr 0.5 -M s of 91 Am 2 / kg is higher than our synthesised n-Al 0 sample (58 Am 2 /kg, taken from M-H loop at 400 kA/m and 100 K) .…”
Section: Microstructural Characterisation Figure 2 Indicates the Larsupporting
confidence: 75%
“…The change of magnetism in HEAs depends on the included elements, which cause a structural change and the formation of a solid solution phase. Recent studies also indicate that the saturation magnetization at room temperature and the Curie temperature of HEAs are both tunable by controlling the concentrations of the principal elements [37]. As an example of the semiconducting properties of HEAs, recent studies found that upon successively adding alloying elements Ge, Pb, and Mn to the SnTe binary alloy to form HEAs, the valence bands and the band gaps in the HEAs are modified as a result of the cocktail effect [38].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they reported that for FeSiBAlNiCo HEAs annealing near re-crystallization temperatures was beneficiatial for the semi-hard magnetic characteristics. [37]. They reported that FeCoNiCrMn and FeCoNiCrSn exhibited paramagnetic behaviour.…”
Section: Effects Of Constituent Elements On Magnetic Characteristics mentioning
confidence: 99%